Analysis of Youtube Content of Mixed-Marriage Women Living Overseas from The Perspective of Anxiety/Uncertainty Management - Genita, Vona Yolanda (Universitas Medan Area, 2024)
The advancement of technology has reduced distance and time constraints, leading to the intercultural marriages experienced by Indonesian women. This research aims to analyze the socio-cultural adjustment of mixed-marriage women from the Anxiety Uncertainty Management (AUM) perspective. Referring to AUM theory, the presence of uncertainty and anxiety serves a significant role in maintaining the focus of mixed-marriage women residing in foreign countries, particularly during cross-cultural interactions. This research utilizes a qualitative content analysis method with the assistance of NVivo 14 Plus to code the distribution of adjustment factors within the YouTube content. The selection of research samples was based on the diversity of husbands' origins, current country of residence, length of marriage, and the depth of women's engagement in sharing personal stories in their content, resulting in the selection of six account owners. The categorization of adjustment factors that emerged in the YouTube video content includes stages of uncertainty management, anxiety management, self-awareness, and effective communication. The results of this research indicate that all women go through the four stages of the AUM model in diverse forms. An additional finding in this study is that support systems play a significant role in assisting women to navigate during the adjustment phases.